(3bUQ GdfRgIs - (3CHh GdMSf Ydj Hf GHi YHO Gddg eMeO GdbQTis; (3GHf haG , Ydj Hf eMeO Hf eMeO GdbQTj GdCfUGQj GdTGPdj, CHh GdMSf,J (B807 (3g` s
(3ChdgG (B:s
(3bGd CHh GdMSf UGMH cJGH GdfRgI jhUi ef hbag Ydi gPG GdcJGH bGd YaG Gddg Yfg jG Hfi EjGc Cf JZT eSdekG aJNQL ef OGjQI GdGSdGe s
(3BNQgG (B:s
(3Gdbhd ai GdMOjO hfYJg hNhGUg hefGaYg hGdhRf ef eGFI KdGKI eKGbjd aEf Pdc fGaY eLQH HEPf Gddg s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi s
Keywords: (3GdcjejGA h GdWHjYjGJs